Ciclagem de nutrientes em cafeeiro arábica conduzido com a Poda Programada de Ciclo e níveis de adubação potássica - Araújo, Diôgo Ribeiro de (2021)
In the management of the coffee tree pruning is essential as it allows for the renewal of the crop, production gains and cycling of part of the nutrients present in the biomass eliminated with the pruning. In this context, the objective was to evaluate the nutrient cycling in Arabica coffee plants conducted with Cycle Programmed Pruning and levels of potassium fertilization. The experiment was carried out in the municipality of Martins Soares - MG, located at 750 m of altitude. A randomized block design with four treatments (K levels at 50, 100, 150 and 200% of the recommended) and four replications for the study of biomass input and nutrient content. For the rate of decomposition and nutrient release, a split-plot scheme was used, in a randomized block design and four replications, with four levels of K in the plot (50, 100, 150 and 200% of the recommended) and nine periods of evaluation in the subplot (30, 60, 90, 120, 150, 180, 240, 300 and 360 days after pruning). The variables total dry mass of leaves of plagiotropic branches per hectare and total biomass of plagiotropic branches deposited per hectare had the lowest averages at the level of 100% K. The deposited biomass ranged from 739.56 kg ha-1 to 919, 85 kg ha-1. The N and Fe contents showed statistically similar effects, and at the 100% K level the lowest averages observed. No significant effect was observed between the levels of fertilization with K and the days after pruning for the remaining mass. Significance was observed as a function of days after pruning, and the remaining mass decreases after 30 days, reaching 78.5% of decomposed leaf material at 324 days. The release of nutrients presented a variable behavior, and at 360 days of evaluation, it was observed release of 46.8% of N, 79.1% of P, 97.2% of K, contained in the leaf biomass, while there was immobilization of 50.4% Cu and 120.9% Zn, in relation to the initial amount of these nutrients contained in the leaves of the pruned branches.